PROFESSIONAL-APPLIED PHYSICAL TRAINING OF FIRST- AND SECOND-YEAR STUDENTS IN THE AREAS OF PRE-CONSCRIPTION MILITARY EDUCATION (American Journal of Pedagogical and Educational Research, 2024)
The article presents an experimentally based program for professionally applied physical training of I-II courses in the direction of pre-conscription military education and the effectiveness of modular training in the educational process at a university.